THU0066 Autoantigenic epitopes targeted by autoantibodies to rna helicase a in systemic lupus erythematosus. (1st June 2001) - Suwa, A; Hirakata, M; Nojima, T; Satoh, S; Nakajima, T; Mimori, T
Abstract : Background: We have previously described new autoantibodies which recognise the 140 kDa polypeptide (p140) in a patient serum with SLE. Recently we have demonstrated that these antibodies are targeting RNA helicase A (RHA) which plays a pivotal role in nuclear events. Objectives: To investigate the target epitopes recognised by autoantibodies to RHA. Methods: Sera from 561 patients with systemic rheumatic disease (287 SLE, 71 SSc, 67 PM/DM, 58 RA, 54 MCTD/overlap, 18 Sjogren syndrome and 6 vasculitis syndrome), and 80 normal humans were screened by immunoprecipitation assay using [35S]-Met-labelled HeLa cell extracts as antigen. In some experiments, [32P]-labelled HeLa cells were used to analyse nucleic acid components. To determine the antigenic epitopes on RHA, restriction fragments of cDNA encoding D1 (amino acids 1–250) containing double-stranded RNA binding domain, D2 (230–650) containing a DEAH box motif, D3 (630–1, 020), and D4 (1, 000–1, 279) containing a glycine-rich region were subcloned into pGEX-2TK vector and expressed in E. coli. The resulting fusion proteins (PD1, PD2, PD3, and PD4) were detected with patient sera. Results: We have found 10 sera which immunoprecipitated a 140 kDa polypeptide from HeLa cell extracts in SLE patients with nephritis. When the precipitated polypeptides were used as antigen in immunoblotting, p140 was recognised by rabbit antisera against RHA. Thus, we have confirmed that all 10 sera contain autoantibodies to RHA. Moreover, it was noted that anti-RHA sera coprecipitated high molecular weight nucleic acids from [32P]-labelled HeLa cell extracts. When cell extracts were treated with RNase, these sera were unable to coprecipitate high molecular weight nucleic acids, indicating that nucleic acid components were RNAs. Under various salt conditions, anti-RHA antibodies were able to coprecipitate nucleic acid components at salt conditions lower than 0.35M NaCl. These results suggested that RHA is interacting with hn-RNA or mRNA. In immunoblotting using the fusion proteins (PD1, PD2, PD3, and PD4), all 10 anti-RHA positive sera strongly recognised PD4. Eight and 9 out of 10 sera recognised PD1 and PD3, respectively, but intensity of binding was variable among different sera. In contrast, none of sera reacted with PD2. Conclusion: Autoantibodies to RHA were identified exclusively in patients with lupus nephritis. The universal epitope was present on the carboxyl-terminal domain of RHA. The reactive patterns of antibodies against multiple antigenic determinants detected here were consistent with the hypothesis that relatively native RHA molecules directly elicit autoantibodies in selected patients.